Delitos Ambientales Por Uso De Agroquímicos Peligrosos O Considerados Como Altamente Tóxicos ¨ - González González, Nelson Eduardo (2016)
When defining to the nature he/she refers it like to the group of the alive beings that in turn understands to the human beings, animals, plants and to the phenomena that take place in a natural way, that is to say, without the man's action or of artificial means as the rain or the snowfalls. Diverse studies, of different commentators mention and they have demonstrated that the use of substances highly toxic agroquímicas is one of the causes of contamination of the environment as for the damage of the floor or fertile layer of the terrestrial layer; since he/she gets lost the native minerals of the floor; likewise, it is harmed to the human's health, to the growth of the flora and the development of the fauna. At the same time the problems that it causes the use of substances highly toxic agroquímicas and the hope of braking to this type of stocks, the State had created legal bodies with the purpose of precautelar the such environment as: The Constitution of the Republic, the Forest Law and of Conservation of Natural Areas and Life Silvestre, The Law of Prevention and Control of Environmental Contamination, Unified Text of Secondary Legislation of Environment, Law of Environmental Administration, norms all in charge ones of to take care and to make respect them rights that he/she has the Nature and that they are not 5 harmed before it is too much afternoon to react before all the natural disasters that can on coming, which would take us to conditions of non experienced lives. To interfere to the problem of what is the contamination on what is the toxic contamination on use of dangerous agroquímicos it is important to carry out a juridical doctrinal study, to be able to determine the existence of the contamination that you/they cause these substances and their incidence in the alive beings. It is also important to inform people on the use of these substances, since these non alone substances affect to the human beings but also to all class of being alive that he/she inhabits the environment for it will be made it a study in our farmers to determine the type and grade of danger that cause these substances when using in the cultivations. Es necesario realizar un estudio y ex activo del código penal para hace poder sancionar mediante una reforma en la que se penalice la incorrecta comercialización y utilización de las sustancias altamente toxicas